2006
DOI: 10.1021/ja057745v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thioether Substituents on the O2 Reactivity of β-Diketiminate−Cu(I) Complexes:  Probing the Role of the Methionine Ligand in Copper Monooxygenases

Abstract: The activation of dioxygen by dopamine β-monooxygenase (DβM) and peptidylglycine α-hydroxylating monooxygenase (PHM) is postulated to occur at a copper site ligated by two histidine imidazoles and a methionine thioether, which is unusual since such thioether ligation is not present in other O 2 -activating copper proteins. In order to assess the possible role of the thioether ligand in O 2 activation by DβM and PHM, two new ligands comprising β-diketiminates with thioether substituents were synthesized and Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 96 publications
3
98
0
Order By: Relevance
“…However, only sideon coordination upon oxygenation of a Cu(I) precursor was indicated by the spectroscopic data [ν(O-O) ) 994 cm -1 ] and by theoretical calculations, which predicted only weak binding of the thioether sulfur atom to copper ( Figure 6). 36 Further ligand perturbations considered with computational modeling involved the introduction of an ancillary ligand whose steric and/or electronic requirements might bias the binding of O 2 in 3 to favor end-on coordination; again, however, no simple, solventlike ligand could be identified that led to the prediction of a thermodynamically stable end-on oxygenated product. 37 Finally, given that the end-on geometry is likely to have more Cu(II)-superoxide character that would be stabilized relative to the Cu(III)-peroxide alternative by a less electron donating supporting ligand, we examined versions of the -diketiminate in 3 with one or two CF 3 replacements for the methyl groups on the backbone.…”
Section: Electronic Structure and Bondingmentioning
confidence: 99%
“…However, only sideon coordination upon oxygenation of a Cu(I) precursor was indicated by the spectroscopic data [ν(O-O) ) 994 cm -1 ] and by theoretical calculations, which predicted only weak binding of the thioether sulfur atom to copper ( Figure 6). 36 Further ligand perturbations considered with computational modeling involved the introduction of an ancillary ligand whose steric and/or electronic requirements might bias the binding of O 2 in 3 to favor end-on coordination; again, however, no simple, solventlike ligand could be identified that led to the prediction of a thermodynamically stable end-on oxygenated product. 37 Finally, given that the end-on geometry is likely to have more Cu(II)-superoxide character that would be stabilized relative to the Cu(III)-peroxide alternative by a less electron donating supporting ligand, we examined versions of the -diketiminate in 3 with one or two CF 3 replacements for the methyl groups on the backbone.…”
Section: Electronic Structure and Bondingmentioning
confidence: 99%
“…Singlet and triplet states were treated at restricted (RDFT) and unrestricted (UDFT) levels of theory, respectively, in keeping with the established methodology for the types of copper-oxygen complexes described herein. 13,28,29,36,37 In addition, UDFT methods were used for doublets and optimizations of Cu(III)-hydroxide complexes. Basis sets utilized included the lacvp** effective core potential basis for Cu [38][39][40] and the double-plus polarization (DZP) 6-31G** basis for all other atoms.…”
Section: Density Functional Calculationsmentioning
confidence: 99%
“…Final electronic energies for singlet states for the full ligand systems are obtained by summing the SCF energies from DFT calculations on the full L 1 and L 2 ligand systems with D for the corresponding simplified model. This methodology has proved capable of predicting both the proper singlet-triplet state orderings 28,29,37 and the kinetics of oxygenation in the L 1 system. 28 To facilitate the determination of D along the reaction path for 1:1…”
Section: Multireference Calculationsmentioning
confidence: 99%
“…[3,4] After electron-transfer, deprotonation, and electron-transfer processes, iminium ion C is produced. Iminium ion C is then converted into enamine D by deprotonation.…”
mentioning
confidence: 99%